Recognition of alpha-mannan by dectin 2 is essential for onset of Kawasaki disease-like murine vasculitis induced by Candida albicans cell-wall polysaccharide. Issue 2 (3rd March 2020) - Oharaseki, Toshiaki; Yokouchi, Yuki; Enomoto, Yasunori; Sato, Wakana; Ishibashi, Kenichi; Miura, Noriko; Ohno, Naohito; Takahashi, Kei
Abstract: Objectives: Using a murine model of systemic Kawasaki disease (KD)–like vasculitis induced by Candida albicans cell–wall–derived mannan · β–glucan · protein complexes, the objective was to elucidate the relationships of β–glucan receptor dectin–1 (D1) and α–mannan receptor dectin–2 (D2) to the onset of that vasculitis. Methods: The incidence and histological severity of vasculitis were compared among mice lacking the genes for D1 or D2 (i.e. D1 −/− and D2 −/− ) and wild–type (WT) mice. Results: The incidences of vasculitis in the three animal groups were 100% (18/18) in the WT group, 100% (18/18) in the D1 −/− group, and 0% (0/18) in the D2 −/− group. In the WT and D1 −/− mice, severe inflammatory cell infiltration, consisting mainly of neutrophils and macrophages, was seen in the aortic root and the coronary arteries. On the other hand, in the D2 −/− mice, not even mild vascular lesions such as endoarteritis were seen. Conclusion: Recognition of α–mannan by D2 played an important role in the onset of vasculitis in the studied murine model.